A comparative study of Spanish adult students' attitudes to ICT in classroom, blended and distance language learning modes. (June 2019) - Arrosagaray, Marcelino; González-Peiteado, Margarita; Pino-Juste, Margarita; Rodríguez-López, Beatriz
Abstract: Fully online and hybrid or blended courses that integrate Information and Communication Technologies (ICT) and complement traditional classroom practice are on the rise nowadays in the field of language teaching. The aim of these courses is to offer flexible learning formats for learners of all ages in the way of tailor-made instruction which can adapt to their needs and expectations. They seem to be suited to diverse educational and social needs and provide, as well as demand, active engagement. There is a large body of research regarding computer supported education, though few studies have compared adult students' attitudes towards ICT in different kinds of courses. Our goal in this study is to analyse and compare adult students' attitudes towards ICT in three different formal learning settings: classroom face-to-face (N = 184), blended (N = 243) and distance (N = 200) language learning modes. We measure and compare the students' self-perceived confidence in digital competence, the ICT impact on their learning and their perception of the learning potential of ICT. Data were collected through a stratified random sample taking the students' learning mode into account and were subjected to descriptive and inferential analyses via SPSS 23.0 software. Results confirm a relationship between students' age, occupation and technology use in general, and between technology use and increased self-perceived confidence in digital competence in the distance language learning mode in particular. On the whole, students acknowledge the beneficial effect or impact of ICT on their learning and expect their learning to be of high value in the future. Highlights: A relationship between students' age, gender, occupation and technology use. A relationship between technology use and students' computer self-efficacy in the distance learning mode. Higher computer self-efficacy does not necessarily entail higher motivation in distance learning.